Physiological, transcriptomic, and metabolomic analyses of the chilling stress response in two melon (Cucumis melo L.) genotypes - Qiannan Diao; Shoubo Tian; Yanyan Cao; Dongwei Yao; Hongwei Fan; Xuejun Jiang; Wenxian Zhang; Yongping Zhang (BMC Plant Biology)
Abstract Background Chilling stress is a key abiotic stress that severely restricts the growth and quality of melon (Cucumis melo L.). Few studies have investigated the mechanism of response to chilling stress in melon. Results We characterized the physiological, transcriptomic, and metabolomic response of melon to chilling stress using two genotypes with different chilling sensitivity (“162” and “13-5A”). “162” showed higher osmotic regulation ability and antioxidant capacity to withstand chilling stress. Transcriptome analysis identified 4395 and 4957 differentially expressed genes (DEGs) in “162” and “13-5A” under chilling stress, respectively. Metabolome analysis identified 615 and 489 differential enriched metabolites (DEMs) were identified in “162” and “13-5A” under chilling stress condition, respectively. Integrated transcriptomic and metabolomic analysis showed enrichment of glutathione metabolism, and arginine (Arg) and proline (Pro) metabolism, with differential expression patterns in the two genotypes. Under chilling stress, glutathione metabolism-related DEGs, 6-phosphogluconate dehydrogenase (G6PDH), glutathione peroxidase (GPX), and glutathione s-transferase (GST) were upregulated in “162,” and GSH conjugates (L-gamma-glutamyl-L-amino acid and L-glutamate) were accumulated. Additionally, “162” showed upregulation of DEGs encoding ornithine decarboxylase, Pro dehydrogenase, aspartate aminotransferase, pyrroline-5-carboxylate reductase, and spermidine synthase and increased Arg, ornithine, and Pro. Furthermore, the transcription factors (TFs), MYB, ERF, MADS-box, and bZIP were significantly upregulated, suggesting their crucial role in chilling tolerance of melon. Conclusions These findings elucidate the molecular response mechanism to chilling stress in melon and provide insights for breeding chilling-tolerant melon.